2011
DOI: 10.4081/ijas.2011.e13
|View full text |Cite
|
Sign up to set email alerts
|

An improved grazed class method to estimate species selection and dry matter intake by cows at pasture

Abstract: Research has recently focused on pasture species intake by ruminants due to their influence on animal product quality. A field-applicable method which investigates species intake and selection, was tested on two dairy cow grazing systems: continuous grazing on a highly-biodiverse pasture (C) and rotational grazing on a moderately-diverse sward (R). In addition to the grazed class method, which evaluates the percentage of grazed dry matter (DM) per species according to the residual height of the plant grazed, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
3
15
0
2
Order By: Relevance
“…In any case, utilisation of a given species by grazing ungulates is affected by many factors, such as vegetative stage, and the presence of other herbaceous species within the pastoral vegetation, as already reported (Orth et al, 1998;Coppa et al, 2011).…”
Section: Wild Ungulates Grazing Selectionmentioning
confidence: 77%
See 1 more Smart Citation
“…In any case, utilisation of a given species by grazing ungulates is affected by many factors, such as vegetative stage, and the presence of other herbaceous species within the pastoral vegetation, as already reported (Orth et al, 1998;Coppa et al, 2011).…”
Section: Wild Ungulates Grazing Selectionmentioning
confidence: 77%
“…If the CDRi/SCi ratio for the i-species is greater than 1, this species is highly selected. A ratio equal to 1 shows that the species is utilized by animals in proportion to its presence, whereas if the ratio is lower than 1, the utilisation of this species is proportionally lower than its availability and the species is considered avoided by animals (Coppa et al, 2011). ANOVA was performed to test the effect of agronomical treatments, year of sampling and their interaction.…”
Section: Methodsmentioning
confidence: 99%
“…For example, cattle will favour patches where they can maximize the intake rate (Distel et al, 1995). Thus, the absence of selectivity for legumes (SI < 1) may be explained by the small size of Trifolium repens and Trifolium pallescens, which protected them from selective grazing (Coppa et al, 2011). Another hypothesis could be the fact that cows frequently pull the leaves with the stem.…”
Section: Discussionmentioning
confidence: 99%
“…This pasture had been grazed at a low stocking rate and had not received any fertilizer applications for the previous 20 years. The botanical composition was reported by Coppa et al (2011a) and cow grazing selection patterns in the two grazing systems by Coppa, Farruggia, Pradel, Lombardi, and Martin (2011b). Plots of the two systems were adjacent.…”
Section: Experimental Design and Animal Managementmentioning
confidence: 94%
“…However, in the case of Cantal cheese, Tornambé et al (2008) showed that the effects of milk terpenes seem negligible, because of their low amounts. Moreover, the grazing systems compared in this experiment, that result from the interactions of botanical diversity and herbage phenology with grazing management and cow selection, could have significantly helped to reduce differences between R and C. Indeed the continuous grazing system enables cows to select more species with high palatability and quality, especially vegetative grasses instead of forbs, like the rotational grazing system, devised to offer cows mainly leafy edible grasses throughout the season (Coppa et al, 2011b). Thus differences in botanical composition and phenology of herbage ingested by cows between R and C may be less important than expected.…”
Section: Sensory Differences In Cheeses From Rotational and Continuoumentioning
confidence: 97%